Picroside II Shows Protective Functions for Severe Acute Pancreatitis in Rats by Preventing NF-κB-Dependent Autophagy. (21st June 2017) - Piao, Xuehua; Liu, Baohai; Guo, Lianyi; Meng, Fanji; Gao, Leming
Abstract : Picroside II, from the herb Picrorhiza scrophulariiflora Pennell, has antioxidant and anti-inflammatory activities. However, its function on severe acute pancreatitis (SAP) and molecular mechanism remains unknown. The effects of picroside II on the SAP induced by cerulean were investigated. SAP rats were treated with picroside II (25 mg/kg). The severity of SAP was evaluated by using biochemical and histological analyses. Pancreatic cancer cell PANC-1 was transfected with ptfLC3 (an indicator of autophagic activity), pcDNA3.1-NF- κ B (nuclear factor kappa B), and pTZU6+1-NF- κ B-shRNA and then treated with picroside II. Relative molecules related with NF- κ B-dependent autophagy were detected by using Western blot. Autophagic activities were observed by phase-contrast and fluorescent microscopes. Acetylated LC3 was detected by immunoprecipitation. The results showed that picroside II treatment reduced the level of ALT, AST, NF- κ B, IL-1 β, IL-6, TNF- α, and SIRT1 (NAD + -dependent deacetylase) and increased the level of SOD and GSH. The autophagic activity was reduced when NF- κ B was silenced, and the levels of TNF- α and SIRT1 were reduced. In contrast, the overexpression of NF- κ B increased autophagic activity and the level of TNF- α, which activated SIRT1. SIRT1 deacetylated LC3 and increased autophagic activities. Picroside II ameliorates SAP by improving antioxidant and anti-inflammtory activities of SAP models via NF- κ B-dependent autophagy.